A study on awareness, occupational risk perception & level of vaccination against hepatitis-B among medical & nursing students in tertiary care hospital, Hyderabad - Pavani, Kalagara; MS, Srinivas Rao; EV, Vinayaraj; Dass, Manick (International Journal of Research in Medical Sciences, 2017)
Background: HBV(Hepatitis B Virus) infection is an occupational hazard for health care workers and the risk of acquiring HBV infections depends on the frequency of percutaneous and permucosal exposure to blood or blood-contaminated body fluids. Avoiding occupational blood exposure is primary preventive means for the transmission of HBV. However, the single most effective measure for the prevention of hepatitis B is active immunisation. Methods: A cross-sectional study was carried among 204 medical and nursing students in second year of their course using pre-designed questionnaire comprised of questions which included age, sex, qualification, awareness, occupational risk perception & vaccination against hepatitis B infection. Results: 69.12% of the respondents knew various modes of transmission of hepatitis B. More than half (56.86%) of the respondents knew that HBV infection causes liver cancer. 79.41% of the respondents knew the correct course of action after a needle stick injury. Only 61.27% of the respondents knew that blood soaked cotton and dressings are discarded in yellow coloured bags and that sharps and needles are disposed in white coloured bags. Only 36.46% of medical students & 57.41% of nursing students were completely vaccinated. Conclusion: Considering the long-term consequences of HBV infection, the health of the study population is at risk. Preventive strategies against the diseases, especially vaccination programmes, should be developed and taken aggressively to improve the vaccination coverage among the study population.